A ressurreição de Jesus Cristo no Evangelho de Marcos: história e querígma! - Sousa, Marcos Adriano de (2014)
The evangelist Mark has presented us Jesus inserted into his vital and historical context, and reveal us all the ressurection teology. The angel's kerygmatic announcement to the women at the tomb transformed the disciples's lives, from weak and fearful men to men willing to spread the announcement of the faith in risen Jesus Christ. From the faith in dead Christ experience, and risen by the Holy Spirit's grace, received in Pentecost, the primitive church is born, which through its testment offers the salvation to all the people and nations. However, from Israel as ellected people and the Petrine primacy, all the nations are invited to the salvation in Jesus Christ universal project. The church, through the kerygmatic ressurection force, is until nowadays at the Nazareth's Jesus follow with all of his teaching. Thus it demonstrates with words, gestures and actions, since its birth, the public life and paschal mistery of Jesus Christ. It's risen Christ driving our faith up to today. That's the meaning of its life and project, which He wants to see carried out at the Galilee of nations. For that, it invites each one of us to look at the life in a brand new way. May the fear of the judgment gives place to the gospel joy, in order to welcome God as friend of life